Intermediaries and learning in sustainability-oriented urban transitions: a transdisciplinary case study from Stellenbosch Municipality - Davies, Megan Lynne (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.